2008
DOI: 10.1002/cjs.5550360110
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate von mises distribution with applications to bioinformatics

Abstract: The methods are applied to real protein data of conformational angles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
134
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(134 citation statements)
references
References 10 publications
0
134
0
Order By: Relevance
“…If we extend the von Mises as a multivariate distribution [3], we face the problem that no closed formulation is known for the normalization term when the number of variables is greater than two, and, therefore it cannot be easily fitted nor compared to other distributions. We introduce a computationally optimized version of the full pseudo-likelihood as well as a circular distance to address these problems.…”
Section: Introductionmentioning
confidence: 99%
“…If we extend the von Mises as a multivariate distribution [3], we face the problem that no closed formulation is known for the normalization term when the number of variables is greater than two, and, therefore it cannot be easily fitted nor compared to other distributions. We introduce a computationally optimized version of the full pseudo-likelihood as well as a circular distance to address these problems.…”
Section: Introductionmentioning
confidence: 99%
“…The non-truncated bivariate von Mises distribution was first proposed by Singh (2002) and extended and developed in Mardia et al (2008) and Mardia and Voss (2011). It is a unimodal/bi-modal function on the torus…”
Section: Bivariate Truncated Von Mises Distributionmentioning
confidence: 99%
“…T he von Mises distribution [20] is the bestknown directional model and can be considered the directional analogue of the univariate normal distribution. Mardia [15,16] introduced a bivariate von Mises distribution and its extension to the multivariate case [17]. He showed that the conditional distributions are also von Mises distributions.…”
Section: Introductionmentioning
confidence: 99%